Corrosion behavior of 9Cr-Si heat resistant steel deposited metal in liquid lead-bismuth eutectic at 550 °C. (1st May 2023) - Liu, Chen; Wei, Shitong; Lu, Shanping
Abstract: The corrosion behaviors of 9Cr-Si heat resistant steel deposited metals with different Si contents in oxygen-saturated static lead-bismuth eutectic at 550 °C were investigated. The results indicates that the oxide scale has a three-layer structure, including outer layer, inner layer, and inner oxidation zone (IOZ). The growing rate of oxide scale decreases with the increasing Si content in steel. The oxidation mechanism of high Si 9Cr deposited metal was discussed. IOZ presents emergence, disappearance, and regeneration in the corrosion process, while the inner layer divides into two sublayers during oxidation. Highlights: The oxide scale presents a three-layer structure and grows by a parabolic law. IOZ presents emergence, disappearance, and regeneration in the corrosion process. The inner layer of oxide scale divides into two sublayers during oxidation. The synergistic effect of Cr and Si enhances the oxidation resistance of 9Cr-Si steel deposited metals in LBE.